Invisible Learnings?: A Commentary on John Hattie's Book - 'Visible Learning: A Synthesis of Over 800 Meta-analyses Relating to Achievement' - Snook, Ivan; O'Neill, John; Clark, John; O'Neill, Anne-Maree; Openshaw, Roger (New Zealand Journal of Educational Studies, 2009)
The review and analysis of the book 'Visible Learning: a synthesis of over 800 meta-analyses relating to achievement' by John Hattie is discussed. John Hattie's book makes a significant contribution to understanding the variables surrounding successful teaching and think that it is a very useful resource for teacher education; however, some issues of concern are highlighted.
Keywords: TICE; numérique